2002
DOI: 10.1111/j.1745-7599.2002.tb00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Community‐Based Three‐Year Breast and Cervical Cancer Screening Program for Medically Underserved, Low Income Women

Abstract: The results from this project provide an example of how advance practice nurses (APNs) can demonstrate meaningful and competitive health care services for underserved women and how APNs can actively evaluate programs they offer that affect the health practices of communities in need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Al-Naggar et al (2009) showed that concerns about the side effects were the reasons for low utilization of mammography screening. Lack of trust in the system and fear are deeply rooted barriers to mammography and other screening procedures (Schulz et al, 2002;Tinley et al, 2004;Powell et al, 2005). Similarly, fear of radiation was significant among women who never had mammography (Allen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Naggar et al (2009) showed that concerns about the side effects were the reasons for low utilization of mammography screening. Lack of trust in the system and fear are deeply rooted barriers to mammography and other screening procedures (Schulz et al, 2002;Tinley et al, 2004;Powell et al, 2005). Similarly, fear of radiation was significant among women who never had mammography (Allen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The health care system itself is often found to be a barrier, due to fragmented care (Schulz et al, 2002), long service wait times (Schulz et al, 2002;Holt et al, 2003;Johansson & Bertero, 2003;Peek & Han, 2004;Tinley et al, 2004;Rauscher et al, 2005;Young & Severson, 2005), and poor interaction with the physician (Young & Severson, 2005). Other barriers that may limit the utilization of mammography as reported by previous studies were embarrassment, low income, lack of health insurance, lack of physician recommendation, lack of trust in hospitals and doctors, language barriers, lack of transportation (Alexandraki and Mooradian, 2010), being a single woman and not having breast related complaints (Nur, 2010).…”
Section: Discussionmentioning
confidence: 99%